COMPARISON OF WHAT IF, FAST TRACK, AND CRASH PROGRAM METHODS FOR ACCELERATION OF PROJECT DELAY - Ratih Prawirawati; Agus Suharyanto; Alwafi Pujiraharjo (Rekayasa Sipil, 2022)
One of the obstacles that often arises in working on a project is project delay. Delays are usually caused by unplanned obstacles Â or problems. Delays cause the project implementation duration is not as planned in employment contract. What If, Fast Track, and Crash Program methods can all reduce project delays. The costs incurred by the Fast Track method and the What If method were less than the realization costs, while the Crash program method is greater than the realization costs, but the costs of all these methods are greater than the planning costs.The combination of Fast Track Crash Program methods and the combination of Fast Track What If methodsboth can restore the initial duration of the project.If the methodsare reversed into combinations of the Crash Program Fast Track methods and What If Fast Track methods, the produced results aredifferent, namely unable to restore the initial duration of the project. The costs incurred from these combinations are both less than the realization costs, but still higher than the planning costs.